Kinetic asymmetries between forward and drop jump landing tasks - Morgana Alves de Britto; Pedro Silvelo Franco; Evangelos Pappas; Felipe P Carpes (Universidade Federal de Santa Catarina, 2015)
Landing asymmetry is a risk factor for knee anterior cruciate ligament injury. The aim of this study was to identify kinetic asymmetries in healthy recreational athletes performing different jump-landing techniques. Twelve recreational athletes engaged in regular training underwent kinetic evaluation using two 3D force plates and were analyzed for: (a) three-dimensional peak forces, (b) time to peak vertical force, and (c) initial phase asymmetries. All data were collected during performance of unilateral and bilateral trials of forward and drop jump tasks. Forward jump-landing tasks elicited greater kinetic asymmetry than drop-landing tasks. Regardless of jump-landing technique, the preferred leg experienced higher forces than the non-preferred leg. The initial landing phase showed more kinetic asymmetries than the later phase when peak vertical forces occur. It was concluded that when screening athletes for kinetic asymmetries that may predispose them to injury, forward jump-landing tasks and the early landing phase might show more kinetic asymmetries than drop jump-landing tasks and the late landing phase, respectively.